2020
DOI: 10.1021/acsmacrolett.0c00299
|View full text |Cite
|
Sign up to set email alerts
|

Vitrimerization: Converting Thermoset Polymers into Vitrimers

Abstract: Thermoset polymers with permanently cross-linked networks have outstanding mechanical properties and solvent resistance, but they cannot be reprocessed or recycled. On the other hand, vitrimers with covalent adaptable networks can be recycled. Here we provide a simple and practical method coined as "vitrimerization" to convert the permanent cross-linked thermosets into vitrimer polymers without depolymerization. The vitrimerized thermosets exhibit comparable mechanical properties and solvent resistance with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 54 publications
5
60
0
Order By: Relevance
“…Vitrimerization starts with a cured network, , and therefore, understanding the influence of original network properties on its reforming and properties is important for predicting and controlling vitrimerized product properties. The DGEBA/anhydride system is the most representative and generally used resin for high-value engineering applications such as aircraft components and wind energy industry because of its low toxicity, excellent processibility, and mechanical properties. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitrimerization starts with a cured network, , and therefore, understanding the influence of original network properties on its reforming and properties is important for predicting and controlling vitrimerized product properties. The DGEBA/anhydride system is the most representative and generally used resin for high-value engineering applications such as aircraft components and wind energy industry because of its low toxicity, excellent processibility, and mechanical properties. …”
Section: Resultsmentioning
confidence: 99%
“…We recently demonstrated the concept of vitrimerization to convert permanently cross-linked thermosets into vitrimer-type dynamic networks via a simple one-step method without depolymerization. 31 The method involves the mechanochemical approach of ball milling the thermoset waste with a proper catalyst to form exchangeable metal−ligand sites. 31 The vitrimerized thermoset reforms the cross-linked network and recovers the properties of the initial thermoset.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The development of vitrimers containing dynamic covalent bonds (DCBs) makes it possible to recycle thermosets under mild conditions [ 8 , 9 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Over the past few decades, researchers have developed an array of vitrimers through incorporating various DCBs (e.g., disulfide [ 25 , 26 ], imine-amine exchange [ 27 ], and hindered urea bond [ 28 ]), among which epoxy vitrimer prepared from the curing reactions of epoxy-anhydride [ 29 , 30 , 31 ] or epoxy-carboxylic [ 32 , 33 , 34 ] is the most investigated vitrimer system. The network topology can be rearranged via transesterification reactions (TERs) between ester bonds and hydroxyl groups at elevated temperatures, leading to the unique properties of materials such as malleability, self-healing, or reprocessability [ 21 , 29 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 Likewise, the seminal work of Montarnal et al, who first reported on vitrimers, has inspired many research groups around the world, each developing ever so compelling chemistry to achieve these unique reprocessable networks. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Unfortunately, many of the strategies highlighted above can prove costly with sometimes exotic and hardto-scale chemistry and often rely upon the collection of waste for further processing or composting in controlled environments. Dishearteningly, a staggering 32% of polymer-based waste escapes that very collection system and the convenience (and sometimes necessity of singleuse plastics as seen during the COVID-19 pandemic) comes in the way of ecological considerations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Christensen et al achieved closed loop recycling of a crosslinked thermoset by utilizing acid‐degradable diketoenamine bonds whereby they could isolate the triketone monomers such that the network reformed with nearly identical properties 8 . Likewise, the seminal work of Montarnal et al, who first reported on vitrimers, has inspired many research groups around the world, each developing ever so compelling chemistry to achieve these unique reprocessable networks 9–24 …”
Section: Introductionmentioning
confidence: 99%